1978
DOI: 10.1007/bf00241388
|View full text |Cite
|
Sign up to set email alerts
|

Localization of glycosyl transferases in plasma membranes from Dictyostelium discoideum

Abstract: Crude membranes from vegetative and aggregation competent cells of Dictyostelium discoideum Ax 2 were separated by a combination of differential and sucrose gradient centrifugation. A fraction mainly containing plasma membranes could be isolated. The high degree of purity was demonstrated by electron microscopy and by the presence of marker enzymes typical for the plasma membrane and the absence of enzymes characteristic for other subcellular compartments. Furthermore surface labelling with radioactive 1--fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Pc 43.2 which was observed only in cytoplasmic face labeled PM is probably radiolabeled actin. Sievers et al (1978) have reported glycosyl transferase activities in the PM of vegetative Dictyostelium cells; nothing is known about the enzyme(s) itself.…”
Section: Discussionmentioning
confidence: 99%
“…Pc 43.2 which was observed only in cytoplasmic face labeled PM is probably radiolabeled actin. Sievers et al (1978) have reported glycosyl transferase activities in the PM of vegetative Dictyostelium cells; nothing is known about the enzyme(s) itself.…”
Section: Discussionmentioning
confidence: 99%